Fabrication of an Ag2S-MoSx/MoNiAg film electrode for efficient electrocatalytic hydrogen evolution in alkaline solution. (September 2021) - Gultom, N.S.; Kuo, D.-H.; Abdullah, H.; Hsu, C.-N.
Abstract: Hydrogen has a vast potential to replace conventional fossil fuels due to its ecofriendly nature, sustainability, and high energy density. In this report, a two-layer Ag2 S-MoSx /MoNiAg film electrode was fabricated by a two-step sputtering technique for enhancing the electrocatalytic hydrogen evolution reaction (HER) under alkaline conditions. It was found that the overpotential of the two-layer Ag2 S-MoSx /MoNiAg film significantly decreased while the current density was dramatically enhanced. The cell overpotentials to reach 10 and 100 mA.cm −2 were 0.16 and 0.28 V for the current densities, respectively. The significant improvement of HER performance of the two-layer Ag2 S-MoSx /MoNiAg as compared to each single layer of Ag2 S-MoSx or MoNiAg was attributed to the synergetic effects of low charge transfer resistance and high electrochemical surface-active area. This two-layer sputtering in material design offers not only a new concept of two-layer heterostructure to enhance the HER but also the simple preparation method with a great prospect for large-scale hydrogen production. Graphical abstract: Image 1 Highlights: An Ag2 S-MoSx /MoNiAg was fabricated by two-step sputtering for efficient HER. Electrocatalytic of Ag2 S-MoSx /MoNiAg greatly enhanced compared to each single layer. This sputtering method has a potential for large-scale application.